Divine Simplicity : a Biblical and Trinitarian Account - Barrett, Jordan P. (Emerging scholars., 2018)
The Christian church has consistently confessed that the triune God of the gospel is simple and therefore beyond composition. The various divine attributes do not represent parts of God that, when combined, make up God's nature. However, what was once part of the theological tradition from Irenaeus to Jonathan Edwards can now be said to have nothing to do with Christian theology. Divine Simplicity engages the recent critics and addresses one of their major concerns: that the doctrine of divine simplicity is not a biblical teaching. By analyzing the use of Scripture by key theologians from the early church to Karl Barth, Barrett finds that divine simplicity developed in order to respond to theological errors (e.g., Eunomianism) and to avoid misreading Scripture. Through close attention to Scripture, the work also argues that divine simplicity has two biblical roots: the names of God and the indivisible operations of the Trinity ad extra. After clarifying its biblical origins, the volume then explains how divine simplicity can be rearticulated by following a formal analogy from the doctrine of the Trinity--the analogia diversitatis (analogy of diversity)--in which the divine attributes are identical to the divine essence but are not identical to each other.